Revealing Dynamic Effects of Mobile Ions in Halide Perovskite Solar Cells Using Time‐Resolved Microspectroscopy. Issue 1 (11th October 2020) - Chen, Weijian; Gan, Zhixing; Green, Martin A.; Jia, Baohua; Wen, Xiaoming
Abstract: Halide perovskites are promising candidate materials for the next generation high‐efficiency optoelectronic devices. Since perovskites are electronic‐ionic mixed conductors, ion dynamics have a critical impact on the performance and stability of perovskite‐based applications. However, comprehensively understanding ionic dynamics is challenging, particularly on nanoscale imaging of ionic dynamics in perovskites. In this review, mobile ion dynamics in halide perovskites investigated via luminescence spectroscopy combined with confocal microscopy are discussed, including mobile ion induced fluorescence quenching, phase segregation in mixed halide hybrid perovskite, and mobile ion accumulation at the interface in perovskite devices. Steady‐state and time‐resolved luminescence imaging techniques, combined with confocal microscopy, are unique tools for probing ionic dynamics in perovskites, providing invaluable insights on ionic dynamics in nanoscale resolution, along with a wide temporal range from picoseconds to hours. The works in this review are not only for understanding mobile ions to improve the design of perovskite‐based devices but also foster the development of microspectroscopic methodologies in a broader solid‐state physics context of investigating ionic transports in polycrystalline materials. Abstract : Dynamic processes of mobile ions, as well as the interaction between charge carriers and mobile ions, are intimately correlated to the observed slow response in perovskites. Photoluminescence (PL) and time‐resolved PL (TRPL) imaging are unique tools to probe the dynamic processes of the slow response and the corresponding microscopic and temporal physical mechanisms.